Management of Zakat Funds in the One Family One Graduate Scholarship Program (SKSS) at BAZNAS OKU - Yose Rizal Fajri; Lovin Aditya P; Nur Hawa (LP2M IAIN Palopo, 2025)
The One Family One Scholar (SKSS) Scholarship Program managed by the National Zakat Agency (BAZNAS) of Ogan Komering Ulu (OKU) Regency is an effective implementation of professional zakat management that aims to improve access and quality of education for students from underprivileged families. This study uses a qualitative descriptive method to analyze the distribution mechanism of professional zakat funds in the SKSS program and its effectiveness in supporting education in OKU. The results show that zakat management is carried out professionally and transparently with strict recipient selection and based on field surveys, supported by coordination between provincial and district zakat institutions and partnerships with educational institutions such as Baturaja University. Zakat funds are distributed in the form of education costs and motivational coaching that have a positive impact on the academic achievement and social readiness of recipients. Regular monitoring and evaluation ensure the sustainability of the program that meets the needs of mustahik. The BAZNAS OKU SKSS program successfully integrates the principles of social justice, managerial efficiency, and empowerment of sustainable education, becoming a replicable zakat management model to strengthen the welfare of the community through education.